The Strengths and Weaknesses of the New Correction of the Translation of the Ghoshirieh Treatise, Published by Sokhan Publication - Alireza Hajianejad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Shortly after the Ghoshirieh treatise was written, it was first translated into Persian by Abu Ali bin Ahmad Osmani for the use of Farsi language speakers, and after a while, the translation was modified or provided with another version. With the help of the Arabic text and based on the manuscripts of Süleymaniye Library_Lala İsmail and British Museum,  Badiozzaman Forouzanfar corrected this book for the first time in 1966. The educational aspects of the book and the emergence of some inadvertences prompted others to provide a further correction of the Arabic original and its Persian translation. Just like and after Mohebbati, Rowzatian and Mirbaqerifard believe that Forouzanfar has made a methodological mistake in his work by comparing two versions of a translation, both of which have been conducted by one translator. Based on the manuscript in the Hagia Sophia museum and by checking it with the manuscript available in the British Museum, they have corrected the Ghoshirieh treatise. Low-false suitable typography and several indexes are the main advantages of this manuscript. The weak aspects of its suspicions, neglecting the introduction of the sources of Arabic distiches and the Arabic text of the work are among the disadvantages of the manuscript besides neglecting its comparison with the Forouzanfar’s manuscript.